2007
DOI: 10.1105/tpc.107.052332
|View full text |Cite
|
Sign up to set email alerts
|

AnUstilago maydisGene Involved in H2O2 Detoxification Is Required for Virulence

Abstract: The fungus Ustilago maydis is a biotrophic pathogen of maize (Zea mays). In its genome we have identified an ortholog of YAP1 (for Yeast AP-1-like) from Saccharomyces cerevisae that regulates the oxidative stress response in this organism. yap1 mutants of U. maydis displayed higher sensitivity to H 2 O 2 than wild-type cells, and their virulence was significantly reduced. U. maydis yap1 could partially complement the H 2 O 2 sensitivity of a yap1 deletion mutant of S. cerevisiae, and a Yap1-green fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(230 citation statements)
references
References 64 publications
4
225
1
Order By: Relevance
“…No accumulation of H 2 O 2 was observed around the tips of penetrating hyphae of the wild type fungus. Treating the host plant with DPI restores the virulence of the deletion mutant (Molina and Kahmann, 2007). These studies exemplify how detoxification of host-derived ROS is essential for fungal virulence and pathogenesis.…”
Section: The Multiple Functions Of Rosmentioning
confidence: 80%
“…No accumulation of H 2 O 2 was observed around the tips of penetrating hyphae of the wild type fungus. Treating the host plant with DPI restores the virulence of the deletion mutant (Molina and Kahmann, 2007). These studies exemplify how detoxification of host-derived ROS is essential for fungal virulence and pathogenesis.…”
Section: The Multiple Functions Of Rosmentioning
confidence: 80%
“…Three papers have brought to the fore the importance of ROS production and scavenging by the pathogen. Egan et al (2007) reported that the generation of ROS by the rice blast fungal NADPH oxidase is required for infection, whereas Molina and Kahmann (2007) documented that activation of ROS scavenging mechanisms by the fungal Ustilago maydis Yap1 gene is essential to overcome the plant defense mechanisms and allow infection. In addition, Mittapalli et al (2007) reported that the ROS scavenging mechanisms of the Hessian fly (Mayetiola destructor) could play an important function in the interaction with its wheat (Triticum aestivum) host.…”
Section: Ros In Biotic Interactions and Responsesmentioning
confidence: 99%
“…Due to their toxicity and importance in plant defense responses, ROS are essential for the progression of fungal infection (Wojtaszek, 1997;Apel and Hirt, 2004). U. maydis yap1, a gene involved in H 2 O 2 detoxification, is required for virulence, and the addition of diphenyleneiodonium (DPI), an inhibitor of the plant NADPH oxidase, restores the normal infectious growth in plant tissues (Molina and Kahmann, 2007). To determine whether the infection defect shown by Dpmt4 cells is somehow related to problems in H 2 O 2 detoxification, 0.5 mM DPI was added to the Dpmt4 cell culture during inoculation.…”
Section: The Inhibition Of Plant Ros Production Does Not Restore Thementioning
confidence: 99%
“…In the DPI treatment, DPI solved in DMSO was added at 0.5 mM directly to the U. maydis strains prior to inoculation. As a control, DMSO alone was added to the strains (Molina and Kahmann, 2007).…”
Section: Pathogenicity Assaysmentioning
confidence: 99%